Strategies to Revive Traditional Decision-Making in the Context of Child Protection in Northern British Columbia - Ney, Tara; Bortoletto, Carla; Maloney, Maureen (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2013)
For indigenous peoples, recovering from colonial rule and aspiring to flourish, the revival of traditional decision making (TDM) is considered essential. However, transitioning from established colonial practices to TDMs is not well understood. In this paper we identify some of the challenges experienced by a First Nation urban community in the north east of British Columbia as they have tried to develop and implement a culturally-relevant child and family-centered traditional decision-making (TDM) process in the context of government-regulated child protection system. Specifically, we problematize a collaborative decision-making strategy—Family Group Conferencing (FGC). FGCs are premised on values of collaboration, participation, and empowerment, and because this strategy shares many of the values and aspirations of Traditional Decision-Making (TDM), there is a temptation to directly download and incorporate FGCs into the TDM model. In this paper we explore five challenges that warrant particular attention in developing TDM model in this contemporary context: 1) power, 2) cultural adaptability, 3) family support and prevention, 4) coordinator “neutrality”, and 5) sustainable support. We conclude with eight recommendations to overcome these challenges while developing TDMs in a child protection context.